Testing a mediation model of teacher caring, grit, and student wellbeing in English as a foreign language students - Zhou, Guanbing (Frontiers in Psychology, 2023)
Introduction This study delves into the influence of perceived teacher caring on the wellbeing of Chinese English as a Foreign Language (EFL) students, with a specific focus on the potential mediating effect of grit. With a sample size of 748 EFL students hailing from diverse Chinese universities, we aimed to shed light on the connections between perceived teacher caring, student wellbeing, and the mediating factor of grit. Methods To address our research questions, we collected data through self-report questionnaires that gauged perceived teacher caring, student wellbeing, and levels of grit. By utilizing structural equation modeling, we were able to rigorously assess both the direct and indirect impacts of teacher caring on student wellbeing. Results Our analysis uncovered a noteworthy and positive correlation between perceived teacher caring and student wellbeing. Furthermore, our findings indicated that grit plays a significant mediating role in this relationship. This suggests that students who exhibit higher levels of grit are more inclined to experience heightened levels of wellbeing. Discussion The outcomes of this study underscore the significance of nurturing positive teacher-student relationships within the EFL context. The identification of grit as a mediator emphasizes its role in fostering enhanced student wellbeing. These findings collectively emphasize the intertwined nature of teacher caring, grit, and student wellbeing. Educators should consider these insights for their teaching practices, while researchers can use this study as a foundation for further investigations in this domain.